2015
DOI: 10.1167/iovs.14-15341
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Corneal Epithelial Heparan Sulfate Leads to Corneal Degeneration and Impaired Wound Healing

Abstract: Corneal epithelial cells require HS for maintaining corneal homeostasis, and the loss of epithelial HS leads to both impaired wound healing and impaired corneal stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Similar findings were observed in the absence and presence of HSV-1, with infection causing a further delay in wound healing. Additional support comes from recent work showing that genetic depletion of heparan sulfate caused impaired corneal wound healing in mice (Coulson-Thomas et al, 2015). As such, our observations indicate that HPSE has a previously unknown role in epithelial cell migration and corneal pathology.…”
Section: Resultsmentioning
confidence: 93%
“…Similar findings were observed in the absence and presence of HSV-1, with infection causing a further delay in wound healing. Additional support comes from recent work showing that genetic depletion of heparan sulfate caused impaired corneal wound healing in mice (Coulson-Thomas et al, 2015). As such, our observations indicate that HPSE has a previously unknown role in epithelial cell migration and corneal pathology.…”
Section: Resultsmentioning
confidence: 93%
“…However, these mice presented no stromal phenotype (Coulson‐Thomas et al . ). Keratocan expression during mouse corneal development starts around embryonic day 12, and Ext1 expression would therefore only be ablated from the keratocytes of these mice approximately around embryonic day 13.…”
Section: The Role Of Heparan Sulphate In the Development Of Ectodermamentioning
confidence: 97%
“…However, the important role HS plays in corneal epithelial development was clearly demonstrated using K14rtTA;TetOcre removing Ext1 from keratin 14 + cells (corneal epithelial cells) (Coulson‐Thomas et al . ). We have recently demonstrated that HS is essential for corneal epithelial stratification (Coulson‐Thomas et al .…”
Section: The Role Of Heparan Sulphate In the Development Of Ectodermamentioning
confidence: 97%
See 2 more Smart Citations